THE VALUES OF SORONG SALA’ TRADITION AS A SOLUTION TO DEVELOP ISLAH FOR THE GENERATION IN THE COVID-19 ERA - Rina Rohayu Harun; Nurjannah Septyanun; Tin Yuliani (istinbath, 2021)
The use of social media today often triggers a war of opinion between its users and sometimes even leads to reporting to the authorities (police). Wars of opinion or differences of opinion occur because there are different views on something that is being discussed, such as the recent presidential election. Solving problems (simple) through legal channels, for some people is the right step, and provides a deterrent effect for the perpetrators. In fact, in the Covid- 19 era like now, the police have very many tasks, ranging from socialization activities on large-scale social restrictions to curbing and prosecuting people who violate the provisions of PP No. 21 of 2020 concerning Large-Scale Social Restrictions (PSBB) in the Context of Accelerating the Handling of Covid-19. The people began to abandon the habit that was carried out by the previous people in this country, that it would be better to solve problems peacefully and to forgive each other, for the sake of more harmonious and peaceful life. Islah can be manifested, one of which is the traditional tradition/local wisdom of sorong sala’ which is known in Tepal village, one of the areas in Sumbawa Regency, West Nusa Tenggara Province, which still adheres to Adat Bersedikan Syara’, Syara’ Bersendikan Kitabullah. This customary tradition is carried out so that the two warring parties can reconcile without involving the authorities. The method used in this research is descriptive qualitative as well as assessing secondary data about sorong sala ‘as well as filling.